1984
DOI: 10.1113/jphysiol.1984.sp015412
|View full text |Cite
|
Sign up to set email alerts
|

Exercise‐induced arterial hypoxaemia in healthy human subjects at sea level.

Abstract: SUMMARY1. We determined the incidence of exercise-induced arterial hypoxaemia and its determinants in sixteen highly trained, healthy runners who were capable of achieving and sustaining very high metabolic rates (maximal 02 uptake = 72 + 2 ml kg-' min-or 4-81 + 0-131 min'). Arterial blood gases and acidbase status were determined at each load of a progressive short-term exercise test and repeatedly during constant-load treadmill running while breathing air and during inhalation of mildly hypoxic, hyperoxic, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
376
9
10

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 516 publications
(426 citation statements)
references
References 28 publications
27
376
9
10
Order By: Relevance
“…Our findings in the exercising dog, that is, that exercise recruits anatomic arteriovenous shunts, despite a previous inert gas study that has not found physiological pulmonary shunt in the dog (32), is consistent with previous human work demonstrating I-P shunt as assessed by contrast echocardiography (1-3), even though prior gas exchange-dependent techniques have not documented substantial right-to-left shunt (4)(5)(6)(7)(8). Indeed, we would suggest that the magnitude of the exercise-induced anatomic arteriovenous shunting in the human may be greater than in the dog (32), because of the larger relative increases in cardiac output, pulmonary vascular pressures, and (a-a)Do 2 typically observed in humans with exercise.…”
Section: Shunt Consequencesupporting
confidence: 68%
See 2 more Smart Citations
“…Our findings in the exercising dog, that is, that exercise recruits anatomic arteriovenous shunts, despite a previous inert gas study that has not found physiological pulmonary shunt in the dog (32), is consistent with previous human work demonstrating I-P shunt as assessed by contrast echocardiography (1-3), even though prior gas exchange-dependent techniques have not documented substantial right-to-left shunt (4)(5)(6)(7)(8). Indeed, we would suggest that the magnitude of the exercise-induced anatomic arteriovenous shunting in the human may be greater than in the dog (32), because of the larger relative increases in cardiac output, pulmonary vascular pressures, and (a-a)Do 2 typically observed in humans with exercise.…”
Section: Shunt Consequencesupporting
confidence: 68%
“…Despite an absence of right-to-left I-P shunt during exercise as determined by functional, gas exchange-dependent techniques (4)(5)(6)(7)(8), there is substantial research documenting anatomic arteriovenous anastomoses in the isolated lung. Studies have demonstrated direct vascular anastomoses between pulmonary arteries and veins in many mammals including cats (9), dogs (9)(10)(11), and healthy humans (9,12,13).…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…During sea-level exercise, some endurance-trained athletes experience arterial hypoxemia [exercise-induced hypoxemia (EIH)] that can be defined as a decrease in both oxygen arterial partial pressure (Pa O 2 ) and arterial hemoglobin saturation during exercise (8). Miyachi and Katayama (21) have reported repeated episodes of EIH during training sessions when endurance athletes performed very intense exercise, a result suggesting that athletes develop frequent episodes of mild hypoxemia during training.…”
mentioning
confidence: 99%
“…It might be worthwhile to discuss the possible actions on the most important functional respiratory parameters. Taking the maximal oxygen consumption (V'O 2 max) as the target of most physical performances, it is known that in the high level endurance athletes, their blood saturation may decrease during heavy or extreme exercise [5][6]. A very good analysis on the possible mechanisms underlying the human aerobic performance and the limit to V'O 2 was carried out by Lindstedt SL and Careley KE [7].…”
Section: Natural Limits To Doping Methods In the Endurance Performancesmentioning
confidence: 99%